International elements in principles and values implement practice by Scope International (M) Bhd. employees / Nurul Dalila Mohd Derus - Mohd Derus, Nurul Dalila (2010)
The purpose of this case study is to understand more about the issue and the elements that the company using to be their principles and values. The principles and values are very important to be a guideline for the employees to do their daily works. Without having a guideline in the company, the company will not succeed like others success company. This study is also to know better about the company while in practical training. The practical training is about 20 weeks is good enough to know better about the company. This project paper helps enough to know better about the company. Furthermore, it also to determine whether there is a gap between the company expected and practice by their employees and also to give suggestion and better solutions to solve the company problem. This is the issue that the company having. This case study help them to know whether their employees really perceived what they have been expected or not. And from the findings, it will help the company to find the solutions to solve their problem. From the findings it shows that there is a gap between company expected and employees perceived. The total average shows that the average gap is 3.80. But the gap is not too big and shows that the data is more to positive disconfirmation which mean the employees still understand what the company wants from them. The employees more to use or implement international and courage of principles and values in doing their daily works. While creative, trustworthy and responsive take place in the lowest rank. When three of these elements take place in the lowest rank, it does not mean that the employees is not understand or did not perceived hundred percent but this is because their daily works are not too involve with these three elements in principles and values.